Dyscyplina postna w Kościele od Kodeksu prawa kanonicznego z 1917 roku - Janczewski, Zbigniew (Śląskie Studia Historyczno-Teologiczne, 1999)
The abstinence and the fast are very important matters in the life in the Church. The law on this cases was changing from the year 1917. First change was after the II Vatican Council. The Constitution Paenitemini of the pope Paul VI from the 1966 year among many noveltys gave for the Bishops Conferences the licence to change the Friday abstinence to another kinds of penance. The next changes are on the Code of Canon Law of the pope John Paul II. This article is also about abstinence from meat in the polish particular law.